A study on the Shariah decision making processes adopted by the Shariah committee in Malaysian Islamic financial institutions - Abdullah, Mohamad Asmadi; Hassan, Rusni; Omar, Muhammad Naim; Mohd Napiah, Mohammad Deen; Othman, Ahmad Azam; Arifin, Mahamad; Yusoff, Adnan (INSI Publications, 2014)
The Shariah Committee is responsible to ascertain that the banking and financial activities of the Islamic financial institution it represents, comply with the principles of Shariah. In fact, the bank has to consult with the Shariah Committee and has to adopt its advice on Shariah matters. Generally, from Islamic law perspective, the original ruling for banking and financial activities is the permissibility, which implies that any business activity is lawful or Shariah compliant unless evidence to the contrary exists.The ruling would change when the prohibited elements are established. This becomes the primary responsibility of the Shariah Committee to determine the ruling of such activities whether they remain lawful or are effectively changed to being prohibited. This would necessitate the Shariah Committee to adopt a specific methodology in order to arrive at the correct decision. This article studies on the Shariah decision making process adopted by the Shariah Committee in Malaysia. The writing also examines the methodology adopted in determining the issues of Shariah compliance of financial instruments. The study also looks into the need of the concerted effort between the Shariah Committee and the industry practitioners so that the requirement of Shariah compliance is fully met in the banking and financial businesses in Malaysia.